Sexually Transmitted Infections: Perceived Knowledge Versus Actual Knowledge - Heather Ferguson; Richard Topolski; Marc Miller (Georgia Southern University, 2006)
Sexually transmitted infections (STIs) continue to be a serious problem, with potentially severe consequences. Past research has found that people may not seek out treatment for STIs because they do not know what symptoms to look for (Greenberg et al., 2002). The present study investigated many aspects of STI knowledge, including perceived knowledge and actually knowledge. Moreover, this study added a novel and applied aspect to the assessment of STI knowledge: visual knowledge. Overall, participants performed poorly on the actual STI knowledge, however, those who rated their knowledge as high performed significantly better than those who rated their knowledge as low. The data revealed two significant predictors of actual STI knowledge, level of STI education and number of previously contracted STIs. In addition, it was found that participants performed better on the written portion of the test than the visual portion of the test. The authors content that increased education may assist in reducing the transmission of sexually transmitted diseases.